Determinants of non-institutional childbirth: Evidence from the Peruvian demographic and health survey - Paola K. Rodrigo-Gallardo; Brenda Caira-Chuquineyra; Daniel Fernandez-Guzman; Diego Urrunaga-Pastor; Rodrigo Alejandro-Salinas; Angie Z. Vasquez-Chavesta; Carlos J. Toro-Huamanchumo (Elsevier, 2023)
Objective: We aimed to evaluate the determinants of non-institutional delivery among women of childbearing age in Peru. Methods: We conducted a secondary analysis of data from the Peru 2019 Demographic and Family Health Survey (ENDES). This multi-stage survey sampling is representative at the urban-rural, regional, and national levels. The outcome variable was place of delivery, collected by self-reporting. Binary logistic regression models were used to assess the factors associated with non-institutionalized delivery. Thus, we estimated crude and adjusted odd ratios (aOR). For the multivariable model, the manual forward selection method and the Wald test were used to obtain a final parsimonious model. Results: The final sample included 14,061 women of reproductive age between the ages of 15 and 49. The prevalence of non-institutional delivery was 7.8 %. Multivariate regression analysis found that having a secondary education (aOR:0.48; 95 % confidence interval [CI]:0.39-0.58) or higher (aOR:0.57; 95 %CI:0.42-0.78); belonging to the second (aOR:0.26; 95 %CI:0.20-0.33), third (aOR:0.28; 95 %CI:0.21-0.38), fourth (aOR:0.21; 95 %CI:0.13-0.33), or fifth wealth quintile (aOR:0.15; 95 %CI:0.09-0.27); and suffering intimate partner violence (aOR:0.76; 95 %CI:0.64-0.91) were associated with lower odds of non-institutional delivery, while not having some type of health insurance (aOR:3.12; 95 %CI:2.47-3.95), living in a rural area (aOR:1.93; 95 %CI:1.54-2.42), and having had three or more deliveries (aOR:1.36; 95 %CI:1.07-1.72), were associated with higher odds of non-institutional delivery. Conclusions: We found that not having health insurance, residing in a rural area, and having had three or more deliveries were factors associated with non-institutional delivery in women of childbearing age. We propose that should focus public health strategies towards providing education to women about maternal health, and likewise, facilitating access to specialized health centers for rural populations.